Managing the Risks of Content Management Systems Adoption (Filenet): A Guide to Risk Analysis and Mitigation - David Lee; Ravikiran Kandepu (International Journal on Orange Technologies, 2023)
Content management systems (CMS) have become a vital technology for organizations to create, manage, and publish digital content through intuitive web interfaces. However, adopting CMS also introduces considerable technological and organizational risks stemming from the integration and workflow changes needed to leverage these platforms. Without identifying and mitigating these risks, CMS initiatives frequently run into major issues around security, costs, user adoption, fragmented workflows, and an overall lack of value realization. This paper provides a comprehensive survey of the most common risks arising during CMS implementation and proven mitigation strategies. The analysis examines risk areas across security, integration complexity, budget overruns, process disruption, inconsistent governance, and user resistance. For each area, prevalent risks are outlined along with industry best practices, frameworks, and guidelines to avoid or minimize potential pitfalls. A structured risk analysis approach is presented, covering how organizations can proactively identify, evaluate, and treat risks throughout the CMS implementation lifecycle. Once risks are visible, mitigation actions can be prioritized and tailored to the organization's needs. Ongoing risk assessment is essential even after launch as new issues emerge. Overarching best practices for managing CMS risks are highlighted based on industry evidence and risk management methodologies. These include establishing clear and realistic requirements, following secure software development lifecycles for customizations, phasing rollouts to simplify integration, budgeting for total cost of ownership, allowing time for user adoption, instituting adaptable governance, maintaining training reinforcement, and continuously monitoring and communicating risks. With holistic risk analysis combined with structured change management, organizations can more confidently embark on CMS initiatives. Potential pitfalls are uncovered early and mitigated through cross-functional collaboration and oversight. Rather than being derailed by foreseeable risks, organizations can tap the full potential of CMS to improve content workflows, automation, and digital capabilities while avoiding major disruptions across people, processes, and technologies. The survey highlights how multifaceted risk management practices enable successful CMS implementation that realizes measurable benefits and impact.